Towards vibrant fish populations and sustainable fisheries that benefit all: learning from the last 30 years to inform the next 30 years - Steven J. Cooke; Elizabeth A. Fulton; Warwick H. H. Sauer; Abigail J. Lynch; Jason S. Link; Aaron A. Koning; Joykrushna Jena; Luiz G. M. Silva; Alison J. King; Rachel Kelly; Matthew Osborne; Julia Nakamura; et al. (Reviews in Fish Biology and Fisheries, 2023)

Thiomicrorhabdus streamers and sulfur cycling in perennial hypersaline cold springs in the Canadian high Arctic - Elisse Magnuson; Nadia C.S. Mykytczuk; Andre Pellerin; Jacqueline Goordial; Susan M. Twine; Boswell Wing; Simon J. Foote; Kelly Fulton; Lyle G. Whyte (Environmental Microbiology, 2021)
Summary The Gypsum Hill (GH) springs on Axel Heiberg Island in the Canadian high Arctic are host to chemolithoautotrophic, sulfur‐oxidizing streamers that flourish in the high Arctic winter in water temperatures from −1.3 to 7°C with ~8% salinity in a high Arctic winter environment with air temperatures commonly less than −40°C and an average annual air temperature of −15°C. Metagenome sequencing and binning of streamer samples produced a 96% complete Thiomicrorhabdus sp. metagenome‐assembled genome representing a possible new species or subspecies. This is the most cold‐ and salt‐extreme source environment for a Thiomicrorhabdus genome yet described. Metaproteomic and metatranscriptomic analysis attributed nearly all gene expression in the streamers to the Thiomicrorhabdus sp. and suggested that it is active in CO 2 fixation and oxidation of sulfide to elemental sulfur. In situ geochemical and isotopic analyses of the fractionation of multiple sulfur isotopes determined the biogeochemical transformation of sulfur from its source in Carboniferous evaporites to biotic processes occurring in the sediment and streamers. These complementary molecular tools provided a functional link between the geochemical substrates and the collective traits and activity that define the microbial community's interactions within a unique polar saline habitat where Thiomicrorhabdus ‐dominated streamers form and flourish.

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Evaluating the effects of climate change in the southern Benguela upwelling system using the Atlantis modelling framework - Kelly Ortega‐Cisneros; Kevern L. Cochrane; Elizabeth A. Fulton; Rebecca Gorton; Ekaterina Popova (Fisheries Oceanography, 2018)
The ocean is affected by multiple anthropogenic stressors including climate change, the effects of which are already evident in many ocean ecosystems. The ABAC uS v2 end‐to‐end model together with climate projections from the NEMO ‐ MEDUSA 2.0 model were used to evaluate the effects of fishing, warming and horizontal and vertical mixing on the southern Benguela upwelling system. Of the drivers examined in this study, warming had the greatest effect on species biomass, with mainly negative effects. The magnitude of the impacts of warming intensified from the RCP 2.6 to the 8.5 emission scenario. Fishing negatively affected demersal and large pelagic fish, which in turn resulted in a biomass increase of forage fish due to a decrease in predation pressure. Water mixing was found to have minor indirect effects on zooplankton biomass and fish. The responses of species and species groups to the combined effects of fishing and warming were approximately equally divided between additive, synergistic and antagonistic. Interpretation of our model results suggests that the southern Benguela system is likely to be affected by climate change, including substantial changes in the abundance of some species important to the region's fisheries. Future planning for fisheries needs to take this into account, including through management that strives to maintain the resilience of key species and the system as a whole. In line with previous studies on the southern Benguela, the results reinforce the importance of including consideration of the indirect and combined impacts of climate change and fishing in management and planning.

Knowledge that Acts: Evaluating the Outcomes of a Knowledge Brokering Intervention in Western Australia’s Ningaloo Region - Kelly Chapman; Fabio Boschetti; Elizabeth Fulton; Pierre Horwitz; Tod Jones; Pascal Scherrer; Geoff Syme (Environmental Management, 2017)

Planning adaptation to climate change in fast-warming marine regions with seafood-dependent coastal communities - Alistair J. Hobday; Kevern Cochrane; Nicola Downey-Breedt; James Howard; Shankar Aswani; Val Byfield; Greg Duggan; Elethu Duna; Leo X. C. Dutra; Stewart D. Frusher; Elizabeth A. Fulton; Louise Gammage; et al. (Reviews in Fish Biology and Fisheries, 2016)

Long-Term Impacts on Macroinvertebrates Downstream of Reclaimed Mountaintop Mining Valley Fills in Central Appalachia - Gregory J. Pond; Margaret E. Passmore; Nancy D. Pointon; John K. Felbinger; Craig A. Walker; Kelly J. G. Krock; Jennifer B. Fulton; Whitney L. Nash (Environmental Management, 2014)